AN MBSE APPROACH TO SUPPORT ORGANISATIONAL REFORM OF THE ROYAL AUSTRALIAN NAVY. Issue 2 (July 2017) - Do, Quoc; Gahan, CMDR Malcolm; Davidson, CMDR Colin
ABSTRACT: This paper presents a unique MBSE approach to enterprise modelling using a combination of IDEF0 functional modelling method. We applied this approach to the modelling of the engineering and administrative processes of the Royal Australian Navy (RAN). We developed the model named Materiel Seaworthiness Functional Master Set (MS FMS). Importantly, the MS FMS initiative drive comes from the top‐down by the Head of Navy Engineering, Rear Admiral Mick Uzzell AM. He wants assurance that all organisational entities in the large and complex environment of Navy, Defence Groups, and Industry are performing the right functions in a coordinated way to continuously deliver seaworthy materiel (ships, submarines and support items). We are piloting an analytical capability using the well‐established Multi‐attribute Value Analysis (MVA) method named the FMS Traffic Light System that aims to facilitate "what if " analysis, ascertain functional health status, and inform high‐level organisational resource allocation and strategic planning to further the quest to balance efficient delivery with efficient resource allocation.